Board Interlocks and Company Outcomes: A Managerial Accounting Case - Diala, Lucy U. (Journal of Accounting and Finance, 2024)
Board interlocks are formed between two company boards when these companies share at least one common director, resulting in a reciprocal relationship from which both partners expect to benefit. Such conditions imply that directors in these interlocks will be less likely to provide strict monitoring oversight (Beckman, Haunschild, Phillips, 2004). This case examines the ethical and governance issues arising from board interlocks. The analysis examines further how board interlocks are less likely to provide strict monitoring functions on firm operations and financial reporting. Participants noted that since board interlocks imply that companies co-share members on their boards in a reciprocal relationship from which both partners expect to benefit, such conditions lead to less rigorous monitoring oversight. Participants also noted that board interlocks may create openings for operational practices with adverse firm outcomes, such as ineffective internal controls over financial reporting.